Safety, Pharmacokinetics, and Pharmacodynamics of the ADAMTS‐5 Inhibitor GLPG1972/S201086 in Healthy Volunteers and Participants With Osteoarthritis of the Knee or Hip. Issue 1 (2nd December 2021) - van der Aar, Ellen; Deckx, Henri; Dupont, Sonia; Fieuw, Ann; Delage, Stephane; Larsson, Staffan; Struglics, André; Lohmander, L. Stefan; Lalande, Agnes; Leroux, Emilie; Amantini, David; Passier, Paul
Abstract: GLPG1972/S201086 is a disintegrin and metalloproteinase with thrombospondin motif‐5 (ADAMTS‐5) inhibitor in development as an osteoarthritis disease‐modifying therapy. We report the safety, tolerability, pharmacokinetics, and pharmacodynamics (turnover of plasma/serum ARGS‐aggrecan neoepitope fragments [ARGS]) of GLPG1972 in 3 randomized, double‐blind, placebo‐controlled phase 1 trials. Study A, a first‐in‐human trial of single (≤2100 mg [fasted] and 300 mg [fed]) and multiple (≤1050 mg once daily [fed]; 14 days) ascending oral (solution) doses, investigated GLPG1972 in healthy men (N = 41; NCT02612246). Study B investigated multiple ascending oral (tablet) doses of GLPG1972 (≤300 mg once daily [fed]; 4 weeks) in male and female participants with osteoarthritis (N = 30; NCT03311009). Study C investigated single (Japanese: ≤1500 mg; White: 300 mg [fasted]) and multiple (Japanese, ≤1050 mg once daily; White, 300 mg once daily [fed]; 14 days) ascending oral (tablet) doses of GLPG1972 in healthy Japanese and White men (N = 88). The pharmacokinetic profile of GLPG1972 was similar between healthy participants and participants with osteoarthritis, with low to moderate interindividual variability. GLPG1972 was rapidly absorbed (median time to maximum concentration, 4 hours), and eliminated with a mean apparent terminal elimination half‐life of ≈10 hours. Steady state was achieved within 2 days of dosing, with minimal accumulation. Steady‐state plasma exposure after 300 mg of GLPG1972 showed no or minor differences between populations. Area under the plasma concentration–time curve (56.8‐67.6 μg · h/mL) and time to maximum concentration (4 hours) were similar between studies. Urinary excretion of GLPG1972 (24 hours) was low (<11%). Multiple dosing significantly reduced ARGS levels vs baseline at all time points for all doses vs placebo. GLPG1972 was generally well tolerated at all doses.